1.1) arcsin(-1) + arccos0 = π + (π/2) = 3π/2
Пусть arcsin(-1) = α, тогда cosα = -1, значит α = π
Пусть arccos0 = β, тогда cosβ = 0, значит β = (π/2)
2) arctg + arctg(- √3) = π/4 + (-π/3) = 1
2. x=±arccosa+2πk,k∈Z .
3.tg(2x) = 2·tg(x)/(1 - tg²(x))
4.cos 5x-cos 7x=0
-2sin 6x*sin (-x)=0(-2 на синус полусуммы углов умножить на синус полуразности углов)
sin 6x=0 или sin x=0
6x=pn, x=pn/6 или x=pn
x=pn/6
5. sin (3x) =1
3х= π/2+2πn
x= π/6 + (2πn)/3
7. sin(3x)-sin(x)=0
2*sin((3x-x)/2)*cos((3x+x)/2)=0
2sin(x)*cos(2x)=0
1) sin(x)=0
x=π*n
2) cos(2x)=0
2x=(pi/2)+pi*n
x=(pi/4)+pi*n/2
Объяснение:
2-3(2x-2)=5-4x
2-6х+6=5-4х
-6х+4х=5-2-6
-6х=-3
Х=-3:(-6)
Х=0,5
1-7(4+2x)=-9-4x
1-28-14х=-9-4х
4х-14х=-9-1+28
-10х=18
Х=18:(-10)
Х=-1,8
5-2x=11-7(x+2)
5-2х=11-7х-14
7х-2х=11-14-5
5х=-8
Х=-8:5
Х=-1,6
10x+9=7x
10х-7х=-9
3х=-9
Х=-9:3
Х=-3
-x-2+3(x-3)=3(4-x)-3
-х-2+3х-9=12-3х-3
-х+3х+3х=12-3+9+2
5х=20
Х=20:5
Х=4
10(x-9)=7
10х-90=7
10х=7+90
10х=97
Х=97:10
Х=9,7
-9(8-9x)=4x+5
-72+81х=4х+5
81х-4х=5+72
77х=77
Х=77:77
Х=1